'We do not rush to the hospital for ordinary wounds (suḷu tuvāla)': A qualitative study on the early clinical manifestations of cutaneous leishmaniasis and associated health behaviours in rural Sri Lanka. - Sonali Dinushika Gunasekara; Nuwan Darshana Wickramasinghe; Suneth Buddhika Agampodi; Manoj Sanjeewa Fernando; Kosala Gayan Weerakoon; Chandani Liyanage; Lisa Dikomitis; Thilini Chanchala Agampodi (Public Library of Science (PLoS), 2023)
Background Knowledge of early clinical manifestations, people's perceptions and behaviours is crucial in preventing and controlling neglected tropical diseases (NTDs). Cutaneous leishmaniasis is an NTD that causes skin lesions and affects millions worldwide. Delayed healthcare-seeking behaviour leading to prolonged treatment periods and complications is rife among people with cutaneous leishmaniasis. This study examined the patient-reported early clinical manifestations of cutaneous leishmaniasis, local interpretations and associated health behaviours within the socio-cultural context of rural Sri Lanka. Methodology/principal findings We conducted a qualitative study among people with cutaneous leishmaniasis in three rural communities in the Anuradhapura district, Sri Lanka. Participants' experiences were explored through a study-bespoke participant experience reflection journal and in-depth interviews. We analysed the data using a narrative-thematic approach. The study included 30 people with cutaneous leishmaniasis (12 females and 18 males) aged between 18 and 75 years. We identified four major themes during the analysis: 1) patient-reported early clinical manifestations of cutaneous leishmaniasis, 2) local interpretations of the early skin lesion(s), 3) associated actions and behaviours, and 4) the time gap between the initial notice of symptoms and seeking healthcare for cutaneous leishmaniasis. Early clinical manifestations differed among the participants, while the majority misinterpreted them as a mosquito/ant bite, pimple, wart, eczema, macule, or worm infestation. Participants undertook different context-specific self-management actions to cure cutaneous leishmaniasis. We identified an average time gap between the notice of symptoms and the first visit to the healthcare facility ranging from three to twelve months. Conclusions/significance Diverse early clinical manifestations, local interpretations, and associated behaviours of people with cutaneous leishmaniasis have led to a substantial delay in healthcare-seeking. The study sheds light on the importance of understanding the manifestations of NTDs within the social context. Our findings will inform designing context-specific health interventions to improve awareness and healthcare-seeking in cutaneous leishmaniasis in rural settings.